Growth After Menarche in Pediatric Inflammatory Bowel Disease. Issue 2 (1st December 2022) - Salguero, Maria V.; Deplewski, Dianne; Gokhale, Ranjana; Wroblewski, Kristen; Sentongo, Timothy; Jan, Aseel; Kirschner, Barbara S.
Abstract : Objectives: Growth impairment in pediatric patients with pediatric onset inflammatory bowel disease (IBD) is multifactorial. Reports on the effect of age at menarche on adult stature in this population are limited. This study investigated the impact of age at menarche, disease-associated factors, and mid-parental height on growth from menarche to final height (FHt) in pediatric patients with Crohn disease (CD) and ulcerative colitis (UC) and IBD unclassified (IBD-U). Methods: Subjects were enrolled from a prospectively maintained pediatric IBD database when IBD preceded menarche and dates of menarche and FHt measurements were recorded. Results: One hundred forty-six patients: CD 112 and UC 30/IBD-U 4. Mean age (years) at diagnosis (10.9 vs 10.1), menarche (14.4 vs 14.0), and FHt (19.6 vs 19.7). CD and UC/IBD-U patients showed significant association between Chronological age (CA) at menarche and FHt (cm, P < 0.001) but not FHt z score (FHt-Z) < −1.0 ( P = 0.42). FHt-Z < −2.0 occurred in only 5 patients. Growth impairment (FHt-Z < −1.0) was associated with surgery before menarche ( P = 0.03), jejunal disease ( P = 0.003), low mid-parental height z score (MPH-Z) ( P < 0.001), hospitalization for CD ( P = 0.03) but not UC, recurrent corticosteroid, or anti-tumor necrosis factor alpha (anti-TNFα) therapy. Conclusions: Early age of menarche was associated with greater potential for linear growth to FHt but not FHt-Z ( P < 0.05). Surgery before menarche, jejunal disease, hospitalization for CD, low MPH, and weight z score were associated with FHt-Z < −1.0. Abstract :